Images of Local Saints in the Wall Paintings of Churches in the Ohrid Archbishopric from the 11th to the Beginning of the 14th Century - Zakharova, Anna V. (Actual Problems of Theory and History of Art, 2024)
The author assesses the role of the images of local saints in the painted churches of Ohrid Archbishopric, basing on the analysis of the Byzantine ensembles from the 11th century to the period of Serbian domination (14th century) and taking into consideration some new data and hypotheses. The survey of surviving wall paintings shows that there were several key moments when the role of the local saints was conceptualized and put forward in purposefully created ensembles that eventually served as landmarks and models. A first attempt was made by the tsar Samuel in the church of St Achilleus (986‒990) on Prespes, thus launching the cult of this saint in the Northen Balkans. The most important landmarks however were the mid-eleventh century cathedral of St Sophia in Ohrid and the church of St George at Kurbinovo (1191) built and painted upon the orders of learned archbishops Leo (1037‒1056) and John Kamateros (1183‒1215). The choice and placement of the images of saints in these wall paintings demonstrated the position of the Byzantine church towards the origins, the status and the mission of Ohrid Archbishopric. The images of the apostles to the Slavs, saints Cyril and Methodius, as well as that of their pupil Clement of Ohrid, take their place in the hierarchy of the Christian saints and become part of this unity. In the end of the 13th century after the break of traditions and the emergence of the autocephalous Serbian and Bulgarian Churches, other attempts were made to reassemble this system. A new synthesis was created in the church of the Virgin Perivleptos in Ohrid. In the main apse the great church fathers were put together with the patriarchs of Constatninople and the leaders of other Churches, local saints of the neighboring Greek metropolies were painted in the diaconicon, yet the honorary place before the altar screen was reserved for the venerated Ohrid hierarchs, saints Clement and Constantine Kavasilas. During the reign on Serbian kings Milutin and Dušan, the attempts to add the Serbian saints to the local ones remain rare in the wall paintings of the Ohrid Archbishopric. The opposite tendency is more apparent: in the 14th century the images of saints Clement and Achilleus become popular elsewhere in the Northern Balkans, whereas in the Ohrid Archbishopric saint Clement ultimately takes the place of its chief saint patron. This work is supported by the Russian Science Foundation (grant 20-18-00294-P) and done at the Research Institute of Theory and History of Architecture and Town Planning — branch of the Central Research and Project Institute of the Construction Ministry of Russia.